2020
DOI: 10.1002/cdq.12233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Career Course on Chinese High School Students' Career Decision‐Making Readiness

Abstract: Career decision-making is a critical task for high school students, yet little is known about how career interventions affect their decision-making skills and self-efficacy. We investigated the outcome of a career intervention in a Chinese high school setting to determine whether it would reduce the difficulties students faced in making a career decision and elevate their self-efficacy in career exploration. A career intervention course was delivered to 413 high school students (228 female, 185 male) who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
4
30
0
1
Order By: Relevance
“…Career readiness helps young people set career goals, plan career paths, improve professional skills and knowledge and follow the designated path (Gates et al, 2018). For Chinese high school students, career readiness is an essential step in the transition from high school to university, as subjects are chosen with a view to enter and select a major at university (Gu et al, 2020). Career maturity and vocational identity are regarded as equivalent to career readiness (Johnson et al, 2014;Babarović et al, 2020): in this context, maturity refers to individuals' readiness to make decisions about a future career (Savickas and Porfeli, 2011), and vocational identity refers to a component of career readiness; namely, establishing a commitment to career choices (Porfeli et al, 2011).…”
Section: Career Readiness and Career Decision-making Difficultiesmentioning
confidence: 99%
“…Career readiness helps young people set career goals, plan career paths, improve professional skills and knowledge and follow the designated path (Gates et al, 2018). For Chinese high school students, career readiness is an essential step in the transition from high school to university, as subjects are chosen with a view to enter and select a major at university (Gu et al, 2020). Career maturity and vocational identity are regarded as equivalent to career readiness (Johnson et al, 2014;Babarović et al, 2020): in this context, maturity refers to individuals' readiness to make decisions about a future career (Savickas and Porfeli, 2011), and vocational identity refers to a component of career readiness; namely, establishing a commitment to career choices (Porfeli et al, 2011).…”
Section: Career Readiness and Career Decision-making Difficultiesmentioning
confidence: 99%
“…Although there have been numerous investigations of the relationship between CDMSE and other variables, most did not account for gender in the CDMSE of high-school students, and the results of the few studies of gender difference in CDMSE were inconsistent. For example, Gu et al investigated the CDMSE of Chinese highschool students and found no gender difference [35], and Jiang recruited undergraduate students from China and South Korea and detected no gender difference [36]. In contrast, according to Abdinoor, young women reported a higher level of CDMSE than young men [27], and according to Kim and Lee, male college students had higher confidence in career decision-making than female students [37].…”
Section: Career Decision-making Self-efficacymentioning
confidence: 99%
“…Under the premise of realizing self-cognition, high school students can stimulate their inner needs and become interested in themselves, thus forming the inner motive force for career exploration (Creed et al, 2007). The career planning education of high school includes five basic contents, such as self-cognition, academic mastery, major exploration, career planning, and life planning (Gu et al, 2020). Through the six steps of "selfawareness, world awareness, the initial establishment of career goals, decision-making, action and implementation, evaluation and adjustment, " students can not only cultivate the ability of career planning with the core of choice ability but also cultivate core skills and excellent character to adapt to future career changes (Rogers et al, 2008).…”
Section: Not Enough Attention To the Career Exploration Of High Schoolmentioning
confidence: 99%
“…Firstly, establish the career exploration beliefs. Due to the characteristics of high school students, taking schools as the main body and teaching through courses is considered as one of the more effective measures to solve the career exploration and future career preparation of Chinese high school students (Gu et al, 2020;Chen et al, 2021). Therefore, this study believes that the knowledge and information of career exploration under NCEE can be taught to high school students through career courses so as to use career-related means to clarify selfawareness, understand their needs and interests, and form a basic methodology.…”
Section: Coping Model Of Career Explorationmentioning
confidence: 99%